Carotid plaque thickness and carotid plaque burden predict future cardiovascular events in asymptomatic adult Americans. (20th October 2017) - Sillesen, Henrik; Sartori, Samantha; Sandholt, Benjamin; Baber, Usman; Mehran, Roxana; Fuster, Valentin
Abstract: Introduction: Prediction of cardiovascular events improves using imaging, i.e. coronary calcium score and ultrasound assessment of carotid plaque. This study analysed the predictive value of two ultrasound measures of carotid plaque size: carotid plaque thickness and carotid and intima–media thickness (IMT). Methods and results: A total of 6102 asymptomatic persons underwent assessment of conventional risk factors and imaging by carotid ultrasound. Carotid plaque burden (cPB) and maximum carotid plaque thickness (cPTmax) were measured from 'cross-sectional sweep' video acquisition of the carotid artery. IMT was measured from distal common carotid artery images. All participants were followed up for ∼3 years, and major cardiovascular events (MACE) were collected and adjudicated. All data were available for 5808 participants, in whom 216 first MACE events were observed. Increasing both cPB and cPTmax were associated with increasing the risk of future MACE when compared with participants without carotid atherosclerosis. Fully adjusted for risk factors, hazard ratios for cPTmax were 1.96 [95% confidence interval (CI) 0.91–4.25, P = 0.015] for primary MACE and 3.13 (95% CI 1.80–5.51, P < 0.001) for secondary MACE, similar to that of cPB. IMT did not improve risk prediction significantly. Non-categorical net reclassification index (NRI) for cPTmax was 0.178 (95% CI 0.027–0.299, P = 0.032) for primary MACE and 0.173 (95% CI 0.109–0.243, P < 0.001) for secondary MACE, which is almost similar to cPB. IMT assessment did not result in significant NRI. Conclusion: The simpler cPTmax predicted cardiovascular events similarly to the more comprehensive cPB, whereas IMT did not. Awaiting true 3D ultrasound technology cPTmax may be a simple useful measure for prediction of future ASCVD.